Approximate Number Sense in Students With Severe Hearing Loss: A Modality-Neutral Cognitive Ability - Ma, Hailin; Bu, Xiaoou; Sanford, Emily M.; Zeng, Tongao; Halberda, Justin (Frontiers in Human Neuroscience, 2021)
The Approximate Number System (ANS) allows humans and non-human animals to estimate large quantities without counting. It is most commonly studied in visual contexts (i.e., with displays containing different numbers of dots), although the ANS may operate on all approximate quantities regardless of modality (e.g., estimating the number of a series of auditory tones). Previous research has shown that there is a link between ANS ability and mathematics, and that this link is resilient to differences in visual experience (Kanjlia et al., 2018). However, little is known about the function of the ANS and its relationship to mathematics abilities in the absence of other types of sensory input. Here, we investigated the acuity of the ANS and its relationship with mathematics abilities in a group of students from the Sichuan Province in China, half of whom were deaf. We found, consistent with previous research, that ANS acuity improves with age. We found that mathematics ability was predicted by Raven score and inhibitory control ability but not visual working memory capacity or Attention Network efficiencies. Even above and beyond these predictors, ANS ability still accounted for unique variance in mathematics ability. Notably, there was no interaction with hearing, which indicates that the role played by the ANS in explaining mathematics competence is not modulated by hearing capacity. Finally, we found that only mathematics ability and age were correlated with ANS ability when controlling for other factors. In fact, hearing capacity was not significantly related to ANS acuity once mathematics ability was taken into account. These results indicate that the ANS is able to develop normally in the absence of auditory experience, and that its relationship with mathematics ability is not contingent on sensory input from hearing.